1999
DOI: 10.1109/75.755047
|View full text |Cite
|
Sign up to set email alerts
|

A new micro-machined millimeter-wave and terahertz snap-together rectangular waveguide technology

Abstract: A novel technique for micro-machining millimeter and submillimeter-wave rectangular waveguide components is reported. These are fabricated in two halves which simply snap together, utilizing locating pins and holes, and are physically robust, and cheap, and easy to manufacture. In addition, S S Sparameter measurements on these structures are reported for the first time and display lower loss than previously reported micro-machined rectangular waveguides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Among them, UV-LIGA [1], PolyStrata TM [2], Silicon-DRIE [3] and thickresist photolithography [4], [5] are the most promising in providing the desired fabrication accuracy for up to 1 THz. LIGA is able to produce all-metal solid structures.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, UV-LIGA [1], PolyStrata TM [2], Silicon-DRIE [3] and thickresist photolithography [4], [5] are the most promising in providing the desired fabrication accuracy for up to 1 THz. LIGA is able to produce all-metal solid structures.…”
Section: Introductionmentioning
confidence: 99%
“…McGrath et al [4] formed an air-filled waveguide channel in silicon, and reported measured losses of around 0.02 dB/mm at 100 GHz. In [5], Digby et al, used a different micro-machining process to form a substrate integrated 100 GHz air-filled waveguide. Their measured data, around 0.05 dB/mm at 100 GHz was slightly higher than that of McGrath, but it was suggested by the authors that the high attenuation might have been due to some of the waveguide walls being only one skin depth thick.…”
Section: Introductionmentioning
confidence: 99%
“…First serious attempts to design THz RWGs came around the year 2000 [192], [337], [338], when several research groups, pioneers in mm-wave, not so technologically mature as these days, started to venture in the sub-mm wave regime, even properly naming these RWG as THz waveguides. From this starting point, either due to manufacturing limitations [339], [338], or inherent structure losses and performance [192], it has been quite common to introduce some modifications on the usual RWG (structure, dimensions and/or modal operation).…”
Section: Metallic (Microwave) Waveguides and Transmission Linesmentioning
confidence: 99%
“…One reason for the first one is that, although at THz frequencies the penetration depth is lower, some new manufacturing techniques are based on thin metal layers that may not reach the penetration depth. The other reason is that wall roughness may be comparable the penetration depth [337], [349]- [353]. The second one arises because assumed metal model properties (very high σ or perfect conduction) may noticeably change due to manufactured surface roughness [354], [342], or microscopic electromagnetic interaction (Drude model of metals [347]) [355]- [348].…”
Section: Metallic (Microwave) Waveguides and Transmission Linesmentioning
confidence: 99%
See 1 more Smart Citation